Species-Specific Biological Effects of FGF-2 in Articular Cartilage: Implication for distinct roles within the FGF receptor family - Li, Xin (2012)
Existing literature demonstrates that fibroblast growth factor-2 (FGF-2) exerts opposing, contradictory biological effects on cartilage homeostasis in different species. In human articular cartilage, FGF-2 plays a catabolic and anti-anabolic role in cartilage homeostasis, driving homeostasis toward degeneration and osteoarthritis (OA). In murine joints, however, FGF-2 has been identified as an anabolic mediator as ablation of the FGF-2 gene demonstrated increased susceptibility to OA. There have been no previous studies specifically addressing species-specific differences in FGF-2-mediated biological effects. In this study, we provide a mechanistic understanding by which FGF-2 exerts contradictory biological effects in human versus murine tissues. Using human articular cartilage (ex vivo) and a medial meniscal destabilization (DMM) animal model (in vivo), species-specific expression patterns of FGFR receptors (FGFRs) are elucidated between human and murine articular cartilage. In the murine OA model followed by intra-articular injection of FGF-2, we further correlate FGFR profiles to changes in behavioral pain perception, proteoglycan content in articular cartilage, and production of inflammatory (CD11b) and angiogenic (VEGF) mediators in synovium lining cells. Our results suggest that the fundamental differences in cellular responses between human and murine tissues may be secondary to distinctive expression patterns of FGFRs that eventually determine biological outcomes in the presence of FGF-2. The complex interplay of FGFRs and the downstream signaling cascades induced by FGF-2 in human cartilage should add caution to the use of this particular growth factor for biological therapy in the future.